Effect of Ficus deltoidea Aqueous Extract on Blood Glucose Level in Normal and Mild Diabetics Rats - Zainal Adam; Muhajir Hamid; Amin Ismail; Shafii Khamis (penerbit ukm, 2007)
Ficus deltoidea, which is locally known as ‘mas cotek’, has been traditionally believed to have hypoglycaemic activity. In this study, hypoglycaemic activity of aqueous extract of Ficus deltoidea in normal and mild diabetic rats (Streptozotocin induced) was evaluated. The extract was administered orally at different doses (100,500 and 1000mg/kg) to both groups in fasting and post prandial state. The result shows that the aqueous extract of Ficus deltoidea did not have any hypoglycaemic activity in normal rats as well as in fasting mild diabetic group. In post prandial mild diabetic rats, aqueous extract of Ficus deltoidea at the dose of 1000 mg/kg show hypoglycaemic activity after 2 (p<0.01), 4 (p<0.05) and 6 (p<0.01) hours extract administration. Metformin, 500 mg/kg also shows hypoglycaemic activity after 2 (p<0.05), 4 (p<0.01) and 6 (p<0.01) hours administration. Therefore, we suggested that mechanism of action of the Ficus deltoidea aqueous extract maybe through enhancement of glucose uptake to muscle tissue and reduce hepatic gluconeogenesis.